Avaliação de um sistema de bombeamento de água alimentado por painéis fotovoltaicos - Michels, Roger Nabeyama (2007)
The current dissertation describes an experiment to evaluate a water pumping system activated by two photovoltaic panels installed at The Federal Technological University of Paraná FTUPR, Medianeira Campus, in the State of Paraná, Brazil. The city of Medianeira s latitude and longitude are 25º17 43 south and 54º03 38 west respectively, with an altitude of 500.7 meters (1,642.72 feet). The system operated in a real working situation, pumping water to a 20 meters (65.62 feet) elevation. Data were collected, from February 2005 to November 2005, by means of a computerized data collector made by Campbell Scientific Inc that made possible collecting and applying irradiance values in the panel plane, generated current and tension, panel temperature, pressure and consume. Data readings were made at a 1-hertz frequency and stored every minute. Through calculi, the system efficiency and energy values and hydraulic strength were obtained. Winter solstice showed 9.58% efficiency with daily pumping of 2,056.44 liters (543.14 gallons) whereas summer solstice confirmed 9.07% efficiency with daily pumping of 2,377.21 liters (627.86 gallons). Winter day s highest efficiency is associated to the lowest temperature in those days compared to summer days, and the factor that prompted larger pumped water consume, during summer days, was related to solar insulation time that is longer if compared to winter days. Total water pumped during the experiment period was 435,042.20 liters (114,900.99 Gallons).